Kesenjangan Pengakuan Hukum Pendidik Paud Nonformal di Indonesia: Analisis Hukum Empiris Terhadap Ketimpangan Profesional - Rino Dedi Aringga; Suhendar Suhendar; Agung Arafat Saputra; M. Amin El Walad Meuraksa (Jurnal Civic Hukum, 2026)
Early Childhood Education (ECE) services in Indonesia are largely delivered through non-formal, community-based institutions. However, the legal framework governing the professional status of non-formal ECE educators remains inconsistent with the formal recognition of non-formal education within the national education system. This condition creates a gap between legal norms and empirical realities, resulting in unclear professional status, limited access to certification, and inadequate welfare protection for educators. This study aims to analyze the legal recognition gap affecting non-formal ECE educators and examine its implications from the perspective of education policy and empirical legal studies. The research employs an empirical legal method with a qualitative approach, using semi-structured interviews, field observations, and document analysis of relevant education regulations. The findings reveal a regulatory inconsistency between the National Education System Law, which recognizes non-formal education, and the Teacher and Lecturer Law, which primarily focuses on formal education. As a result, non-formal ECE educators remain structurally marginalized, often categorized as volunteers, with limited access to certification and professional development opportunities. This situation reflects a broader structural inequality within the education system. This study contributes to the literature by framing the issue of non-formal educator professionalization within the gap between das sollen and das sein, an approach that remains underexplored in previous research. Therefore, regulatory reform is necessary to establish inclusive professional recognition, equitable certification mechanisms, and sustainable governance of non-formal ECE within the national education system.